ANALISIS TINGKAT KEPUASAN PUBLIK TERHADAP PELAYANAN RUMAH SAKIT BERDASARKAN METODE FUZZY TOPSIS MCDM - Azizah, Nuril Lutvi; Prasojo, Bayu Hari; Rini, Chylen Setiyo (Universitas Dr. Soetomo, 2019)
One of the National Development efforts in the health sector is the availability of adequate and quality health services. These qualities can be seen from several indicators, one of which is the level of patient satisfaction in providing health services. This study aims to provide an evaluation of public satisfaction with hospital services with a case study of several private hospitals in Sidoarjo Regency, so that it can be used as an evaluation or input in assessing hospital internal quality standards based on predetermined selection criteria. The method to be used is Fuzzy Multi-Criteria Decision Making (FMCDM) and TOPSIS which is used to conduct numerical, logic, and analytical scales. From the results of fuzzy analysis of the average 5 aspects, namely tangible, Reliability, responsiveness, assurance, and empathy is 13,29 for RSI Siti Hajar Sidoarjo with an average weight of 0.2 and the quality is still at the level of 5.3 and the fuzzy at Delta Surya Hospital Sidoarjo is 11.74 with an average weight of 0.2 and the quality is still at the level of 4.67 which means both hospitals it is still in the category standard and the relationship in service still needs improvement.